Engineering Structure and Stability of Next-Generation Perovskite Materials for Optimization of Photovoltaic Solar Cell Efficiency - Anugrah; Rismen Sinambela (CV. Get Press Indonesia, 2026)
Perovskite solar cells (PSCs) are a promising next-generation photovoltaic technology due to their high power conversion efficiency (PCE) and facile fabrication. However, structural instability, environmental sensitivity, and operational degradation limit their practical applications. This study investigates the effects of compositional and interfacial engineering on PSC performance and stability. Three perovskite types mixed-cation, interface-modified, and anti-perovskite were fabricated and characterized in terms of crystallinity, morphology, optical absorption, and electrical performance. Mixed-cation perovskites exhibited superior crystallinity, homogeneous morphology, broad optical absorption, the highest PCE (21.0 ± 0.3%), and 86.7% efficiency retention after 500 hours. Interface-modified PSCs enhanced Voc and fill factor, whereas anti-perovskites showed the lowest performance due to poor crystallinity and secondary phase formation. These findings indicate that combining cation/anion compositional engineering with interface modification is an effective strategy for developing high-performance and stable PSCs, offering insights for next-generation photovoltaic device optimization